Preparation of Cellulose Acetate Nanocomposite Films Based on TiO2-ZnO Nanoparticles Modification as Food Packaging Applications - Hajer Ali; Nahida Hameed (Journal of Applied Sciences and Nanotechnology, 2022)
To develop bio-packaging materials, nanocomposite films of cellulose acetate reinforced with titanium dioxide and zinc oxide nanoparticles were prepared, by the casting method at different weight ratios of ZnO nanoparticles (1.5, 2, and 2.5) wt% and a constant weight ratio of 2 wt% TiO2. ZnO and TiO2 nanoparticles were tested using scanning electron microscopy (SEM). The mechanical properties (tensile strength and elongation) were improved at a fixed level of Cellulose Acetate+ 2% TiO2+1.5wt% ZnO loading. Beyond that level of loading, they decreased. The tensile strength was decreased due to some degrees of agglomeration of filler particles above a critical content. Fourier-Transform Infrared Spectroscopy (FTIR) was conducted to reveal the microstructures and chemical composition of as-prepared composite films. The wettability of the films was also determined by the sessile drop method. An increase in contact angle was also observed by the addition of ZnO content from 70.6° to 77.1° compared to pure Cellulose Acetate, which indicated a value of 61.3°. Antibacterial activity against Escherichia coli and Staphylococcus aureus was enhanced after incorporation of ZnO-TiO2 compared with pure CA. The enhanced wettability and antibacterial activity of the prepared films suggest that they could be used for packaging applications.